Congenital Anomalies - From the Embryo to the Neonate 2018
DOI: 10.5772/intechopen.72628
|View full text |Cite
|
Sign up to set email alerts
|

Congenital Anomalies in Human Embryos

Abstract: Morphogenesis mainly occurs during embryonic stage, and congenital anomalies also occur at that time. The Kyoto Collection, one of the largest collections of human embryos, including a lot of those with congenital anomalies, is significantly helpful for analyzing embryonic growth. From the collection, normal and abnormal embryos have been selectively presented in this chapter. Recently developed imaging technology enabled three-dimensional (3D) imaging of embryos and fetuses in high resolution. The devices ava… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 79 publications
(76 reference statements)
0
1
0
Order By: Relevance
“…9,16,18,19 The difference in the mean angle value occurs because of an ear abnormality (low set ear), which causes the ears of people with down syndrome to be rotated and lower than those of normal individuals. 20 Low set ear is found in 58.33% of the sample. This result is similar to the study of Azman et al 21 that is, the low set ear was found in 56.1% of the sample.…”
Section: Discussionmentioning
confidence: 97%
“…9,16,18,19 The difference in the mean angle value occurs because of an ear abnormality (low set ear), which causes the ears of people with down syndrome to be rotated and lower than those of normal individuals. 20 Low set ear is found in 58.33% of the sample. This result is similar to the study of Azman et al 21 that is, the low set ear was found in 56.1% of the sample.…”
Section: Discussionmentioning
confidence: 97%